2018
DOI: 10.1016/j.ijscr.2018.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic portal venous gas after colonoscopy: A case report and review

Abstract: HighlightsHere we reported a rare case of hepatic portal venous gas with a relevant review of literature.Actually the mechanism of HPVG is still unknown.The case present in literature are few and the mortality, generally caused by complications like necrotizing enterocolitis, is still high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…If none of these factors are present, close monitoring is enough for other causes of HPVG. 16,17 Our case showed characteristics of HPVG, with the probable causes being chemotherapy and steroids after ruling out all other causes, and the patient was managed conservatively with a good outcome.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…If none of these factors are present, close monitoring is enough for other causes of HPVG. 16,17 Our case showed characteristics of HPVG, with the probable causes being chemotherapy and steroids after ruling out all other causes, and the patient was managed conservatively with a good outcome.…”
Section: Discussionmentioning
confidence: 76%
“…14,15 Patients with PI and clinical evidence of peritonitis or bowel perforation, old age, postoperative patient, recent vascular graft, surgery, hypercoagulable state, uncontrolled diabetes, and hypertension need careful evaluation to rule out bowel ischemia. 15,16 Worsening leukocytosis, increasing acidosis, and elevated lactates are red flag signs of bowel ischemia and/or gangrene. Radiological findings showing gas under the diaphragm, mechanical obstruction/strangulation, intra-abdominal abscess, and PI are indicators of need for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Last year, our group published a case report and literature review of HPVG [2]. In our case, "a computed tomography scan showed little perianastomotic collections with air-fluid levels and massive hepatic portal venous gas. "…”
Section: To the Editormentioning
confidence: 91%
“…Last year, our group published a case report and literature review of HPVG [ 2 ]. In our case, “a computed tomography scan showed little perianastomotic collections with air-fluid levels and massive hepatic portal venous gas.” Furthermore, in our literature review, we reported a paper that presented a case of HPVG with anastomosis leakage [ 3 ].…”
mentioning
confidence: 99%
“…The unique aspect of our case was that HPVG developed as a surgical complication immediately after colon resection. Capolupo et al [ 3 ] reported an HPVG case that developed at an ileoanal anastomosis site constructed 8 years prior and the cause of HPVG was an endoscopic procedure. Li et al [ 4 ] reported HPVG that developed due to colon cancer obstruction and perforation.…”
mentioning
confidence: 99%